ETO, fusion partner in t(8;21) acute myeloid leukemia, represses transcription by interaction with the human N-CoR/mSin3/HDAC1 complex - Wang, Jianxiang (The National Academy of Sciences, 1998)
The t(8;21) translocation between two genes known as AML1 and ETO is seen in approximately 12–15% of all acute myeloid leukemia (AML) and is the second-most-frequently observed nonrandom genetic alteration associated with AML. AML1 up-regulates a number of target genes critical to normal hematopoiesis, whereas the AML1/ETO fusion interferes with this trans-activation. We discovered that the fusion partner ETO binds to the human homolog of the murine nuclear receptor corepressor (N-CoR). The interaction is mediated by two unusual zinc finger motifs present at the carboxyl terminus of ETO. Human N-CoR (HuN-CoR), which we cloned and sequenced in its entirety, encodes a 2,440-amino acid polypeptide and has a central domain that binds ETO. N-CoR, mammalian Sin3 (mSin3A and B), and histone deacetylase 1 (HDAC1) form a complex that alters chromatin structure and mediates transcriptional repression by nuclear receptors and by a number of oncoregulatory proteins. We found that ETO, through its interaction with the N-CoR/mSin3/HDAC1 complex, is also a potent repressor of transcription. This observation provides a mechanism for how the AML1/ETO fusion may inhibit expression of AML1-responsive target genes and disturb normal hematopoiesis.